ANALISIS PERMINTAAN HUNIAN USAHA HOTEL BERBINTANG DI KOTA PEKANBARU - Agus Leonardo; Wahyu Hamidi; Eka Armas Pailis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in the city of Pekanbaru to consumers who use the services of five-star hotel occupancy. This study aims to determine the factors that influence the level of demand for five-star hotel occupancy in the city of Pekanbaru.The population in this study amounted to 428 506 with a sample of 100 where the sample was determined by the Slovin method. The data used is derived from primary and secondary data is obtained from the BPS and Pekanbaru City Tourism Office and questionnaires. The method used is descriptive analysis of data collection to answer questions regarding the status of current research on this subject. Descriptive data are generally collected through the data collection methods interview or observation. The results showed that the factors of five-star hotel occupancy demand is price, income, and quality of service. From the data obtained from consumers by using a questionnaire , the request that the third factor price, income, and quality of service are in accordance with the five-star hotel occupancy demand analysis using a Likert scale outlined in the continum line.Keywords : hotel demand, prices, income, quality of service